A Handbook to Agra and the Taj : Sikandra, Fatehpur-Sikri and the Neighbourhood - Havell, E. B., (Brill | Manohar Publishers & Distributors, 2024)
In 1558, Akbar established Agra (formerly known as Akbarabad) as the capital of the Mughal Empire. This city was founded by Sikandar Lodi in 1504-5, but it gained prominence under the Mughals. This book describes the numerous structures built by the Mughals and later till the 1857 Mutiny. The author conducts a study around the Mughal monuments in Agra, Fatehpur-Sikri, and Sikandra region, such as Agra Fort, Fatehpur-Sikri complex, Taj Mahal, Itimad-ud-Daulah's tomb, and other minor attractions. This book primarily deals with the architectural styles adopted by the Mughals during Akbar's reign and his successors. This is of greater interest to students, researchers, and instructors interested in medieval Indian architecture, Indo-Islamic architecture, and archaeology.